The Use of a PEG/Ascorbate Booster Following Standard Bowel Preparation Improves Visualization for Capsule Endoscopy in a Randomized, Controlled Study - Mascarenhas-Saraiva, MJ (2021)
Submitted by Helena Donato (bibliotecacuf@jmellosaude.pt) on 2021-07-13T21:56:48Z No. of bitstreams: 1 Use of a PEG.pdf: 936614 bytes, checksum: 1919c8ab31ba091520c466d413a8ddfa (MD5)